Fly wing morphology study with geometric morphometrics - Razak, Ruqayyah (Universiti Sains Malaysia, 2016)
Wings of blowfly species Chrysomya megacephala were collected and examined with Geometric morphometric (GMM) using landmark-based method. This species of Calliphoridae was chosen as it is abundant in Kelantan. The species of C. megacephala is important in forensic work as this species is commonly found in forensic cases involving dead bodies. The examination of wing is focused on wing venation pattern to differentiate wing shape and wing variation between male and female flies. The total number of wings (n = 136) of 68 flies from 12 male flies (n = 24) and 56 females fly (n = 112) were obtained and scanned. Landmark configuration (x, y) were made on all wings and analyzed with Principal Component Analysis (PCA). Procrustes ANOVA was utilized to detect any measurement error by analyzing the centroid size and shape variation of sample. The small value of the measurement error (0.2%) indicated high accuracy of landmarks selected for this research. Sex could be easily differentiated based on the morphology of the wings based on GMM analysis. The PC1 and PC2 from the PCA contributes to 41.5% of the total eigenvalue scores. In conclusion, there is morphological sexual differences between in the C. megacephala wing shape.